Divine Freedom and the Being of the Only-Begotten Son according to St Cyril of Alexandria - Rusev, Rosen (Forum Theologicum Sardicense, 2025)
The main topic of this article is the question of the Fatherhood of God: Is God a Father by nature or by will? The examination of this issue, as provided by St. Cyril of Alexandria, is the focus of this research. The study of his position is conducted in comparison with earlier Christian tradition, with significant emphasis on St. Athanasius and Origen. Additionally, the pagan philosophical tradition is referenced, primarily through the writings of Aris-totle and Plotinus.